Changing and challenging roles of librarians in the knowledge-based economy/ Norilyah Othman - Othman, Norilyah (2012)
This paper outlines the changing and challenging roles of librarians in the knowledge-based economy. In a dynamic, information and technology-driven society, librarians can create new roles by accessing changes in their environment, the potential effect and ways to reposition themselves. New roles, changing roles, and the future of librarians have been debated on for many decades. In knowledge-based economy, there will always be changes in the environment, and these changes will affect librarians: their role, job opportunities, self-image, motivation and even survival. Librarians therefore need to find a solution to timely repositioning and role claiming.